The negative impact of missing primary teeth with the importance of space maintainer among children attending the college of dentistry, hawler medical university in Erbil: Iraq. - Hozan Farid Tawfiq; Alaa Mahmud Mustafa (Erbil Dental Journal)
Background and Objectives: Premature tooth loss can cause undesirable tooth movement, resulting in space loss in the permanent teeth. The space maintainer is a tool-based procedure that is used in both preventive and corrective orthodontics. to examine the impact of primary tooth loss on arch dimensions in children aged 5 to 13 years old, as well as to assess the prevalence of various space maintainers among children attending the pedodontics department at Hawler Medical University's College of Dentistry. Methods: This was a retrospective study in which data was collected utilizing case sheets from patients who visited the pedodontics department at Hawler Medical University's college of dentistry. The data was collected from September 2020 to May 2021 and consisted of 815 case sheets, with 395 boys and 420 females ranging in age from 5 to 13 for both genders. The number of missing teeth, the site of missing teeth (whether it is from the upper or lower arch), the quadrant of missing teeth, and the types and location of space maintainers that were made for the patients were all recorded as demographic data. Using the SPSS software for statistical analysis by IBM of version 26 in which frequency table and Fisher Exact test was used and the level of significance was set at 0.05. Results: With a P-value of 0.016, there was a significant difference in missing teeth among different age groups of the sample, with the most missing teeth found among 6-12 year - old. When there was at least one tooth missing or extracted, the most common type of space maintainer was band and loop (0.6 percent of the cases), and there was no significant difference between male and female of the sample (P- value= 0.477). When there was at least one tooth missing or extracted, there was a significant difference between teeth in the upper left side of the dental arch, and the most common type of space maintainer was band and loop (0.6 percent of the cases). According to the results of the study, patients aging 6 to 12 years old were more likely to have space maintainers constructed in the lower left side of the dental arch. Conclusions: The study draws attention to the fact that space maintainers are used in pediatric dentistry as a part of preventive orthodontics. the most common type of space maintainer was band and loop in the age group 6-12 years.